2002
DOI: 10.1176/appi.ajp.159.4.615
|View full text |Cite
|
Sign up to set email alerts
|

Age, Gender, and Ethnicity Differences in Patterns of Cocaine and Ethanol Use Preceding Suicide

Abstract: Intoxicant use preceding suicide occurred in specific age-, ethnic-, and gender-based patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
1
12

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 13 publications
4
47
1
12
Order By: Relevance
“…Previously we reported that rates of ethanol and cocaine use preceding suicide differed by demographic group, with a larger proportion of whites than blacks having used alcohol before death and more blacks having used cocaine (16). Within each ethnic group, the two genders were essentially identical in rates of presuicide alcohol or cocaine use.…”
Section: Discussionmentioning
confidence: 74%
“…Previously we reported that rates of ethanol and cocaine use preceding suicide differed by demographic group, with a larger proportion of whites than blacks having used alcohol before death and more blacks having used cocaine (16). Within each ethnic group, the two genders were essentially identical in rates of presuicide alcohol or cocaine use.…”
Section: Discussionmentioning
confidence: 74%
“…La mayoría de los estudios realizados en Chile exploran el consumo de sustancias de abuso en adolescentes sobre los 12 o 13 años 3,27,31,[40][41][42][43] . Estudios muestran que a más temprana edad el inicio del consumo de alcohol, mayor es la probabilidad de tener problemas asociados al consumo excesivo de alcohol en la adolescencia tardía 18 , de dependencia a sustancias en la edad adulta 18 , suicidio 44 , violencia 45 y problemas conductuales 5 . Además, el inicio precoz del uso de alcohol o tabaco tienen un mayor riesgo de bajo rendimiento académico 46,47 .…”
Section: Discussionunclassified
“…Only recently have researchers been able to outline a more detailed profile of Blacks most at risk for suicide completion. Conwell, 2004;Garlow, 2002;Marzuk et al, 1992), poor social support (Joe et al, in press;Kaslow et al, 2004;Kimbrough, Molock, & Walton, 1996), family dysfunction (Fernquist, 2004;Ialongo et al, 2002;O'Donnell, O'Donnell, Wardlaw, & Stueve, 2004;Summerville, Kaslow, Abbate, & Cronan, 1994), and access to firearms (Joe & Kaplan, 2002;Kaplan & Geling, 1998). In spite of such empirical advances, little is known as to why Blacks have experienced changes in their rates of suicide.…”
mentioning
confidence: 99%